Investigating Primary School Teachers’ Perceptions about Professional Development and its Impact on Students Achievement (Journal of Social Sciences Review, 2023)
This investigation sought to find out how primary school teachers felt about the value of professional development and how it affected students' academic achievement. Specifically, the researchers were interested in how teachers perceived the value of professional development. The researchers utilized a quantitative research methodology and a self-developed survey questionnaire in order to collect data for the purpose of evaluating teachers' professional development and students' academic success. This allowed the researchers to accomplish the goal of the study and fulfil its purpose. The data were analyzed through SPSS and Smart PLS. According to the study's findings, teachers expressed their level of satisfaction with the effectiveness of professional development at all levels because all three hypotheses were supported, which showed that there is a positive significant effect of effective teaching strategies, well planning and subject-matter knowledge on students' achievement. The study recommends that professional development programs should be enhanced and integrate new technologies for the capacity building of teachers at school levels in the province. On the basis of the conclusion, it is further recommended that academicians and higher authorities should take attentive steps to enhance professional development models as per the need of the 21st century with critical thinking, integration of new technologies and 21st-century skills for better teaching-learning.
Keywords: Professional Development; Subject Knowledge; Effective Teaching; Student’s Achievement